2022
DOI: 10.1021/acsami.2c12666
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Coating to Inhibit Surface Crystallization of Amorphous Pharmaceutical Powders

Abstract: Preventing crystallization is a primary concern when developing amorphous drug formulations. Recently, atomic layer coatings (ALCs) of aluminum oxide demonstrated crystallization inhibition of high drug loading amorphous solid dispersions (ASDs) for over 2 years. The goal of the current study was to probe the breadth and mechanisms of this exciting finding through multiple drug/polymer model systems, as well as particle and coating attributes. The model ASD systems selected provide for a range of hygroscopicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 72 publications
3
16
0
Order By: Relevance
“…The Al 2 O 3 coatings were applied to prepare samples with thinner and thicker coatings. Thickness measurements were broadly consistent when estimated by TGA or imaged by TEM (Table , Figure ), and coatings appear highly conformal, consistent with our previous work. , …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The Al 2 O 3 coatings were applied to prepare samples with thinner and thicker coatings. Thickness measurements were broadly consistent when estimated by TGA or imaged by TEM (Table , Figure ), and coatings appear highly conformal, consistent with our previous work. , …”
Section: Resultssupporting
confidence: 88%
“…Further experiments which explore coating process controls and deposition rates may shed more light on this finding in the future. Our previous works have demonstrated that the coating effectively inhibits surface crystallization, , and our current investigation has shown that the coatings must be sufficiently permeable to water to facilitate rapid release. Combined, this requirement suggests that the optimal coating qualities consist of a relatively thin coating with a sufficient level of defects to facilitate both crystallization inhibition and dissolution performance.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations